1998
DOI: 10.1080/002689798167485
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-chemical theories of associated liquids

Abstract: It is shown how traditional development of theories of fluids based upon the concept of physical clustering can be adapted to an alternative local clustering definition. The alternative clustering definition can preserve a detailed valence description of the interactions between a solution species and its nearneighbors, i.e., cooperativity and saturation of coordination for strong association. These clusters remain finite even for condensed phases. The simplest theory to which these developments lead is analog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…6,7 QCT gets its name because the factors K i ͑n͒ in Eq. ͑11͒ assume the form of equilibrium constants for pseudochemical binding reactions for one ion and n solvent molecules.…”
Section: Ion Solvation and Constrained Coordination Shellmentioning
confidence: 99%
See 3 more Smart Citations
“…6,7 QCT gets its name because the factors K i ͑n͒ in Eq. ͑11͒ assume the form of equilibrium constants for pseudochemical binding reactions for one ion and n solvent molecules.…”
Section: Ion Solvation and Constrained Coordination Shellmentioning
confidence: 99%
“…͑11͒ and ͑13͒ differs somewhat from the standard QCT literature. 6,7 Here, our starting point with Eq. ͑6͒ consists of inserting ␦ n,n Ј in the configurational integral to sort out the number of solvent molecules in the inner-shell region, which is treated as a small open system in equilibrium with a bath of solvent molecules.…”
Section: Ion Solvation and Constrained Coordination Shellmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The present report employs coarse-grained models of colloidal protein-protein interactions to solve for the free energy and structure of clusters using a cell-based, quasichemical ͑QC͒ theory. [18][19][20][21][22][23][24][25] Previous work showed that the QC theory was quantitatively accurate for predicting cluster free energies in simple lattice systems up to typical experimental volume fractions ͑ϳ10 −2 ͒ for protein solutions. 26 The osmotic second virial coefficient ͑B 22 ͒ has been used as a tool to quantify the average magnitude and sign of interactions between protein molecules in dilute solution, [27][28][29][30] although it is not, per se, a direct predictor of standard free energies of association.…”
Section: Introductionmentioning
confidence: 99%